Zombie economics : how dead ideas still walk among us - Quiggin, John (Princeton University Press, 2012)
"In the Graveyard of economic ideology, dead ideas still stalk the land. The recent financial crisis laid bare many of the assumptions behind market liberalism--the theory that market-based solutions are always best, regardless of the problem. For decades, their advocates dominated main stream economics, and their influence created a system where an unthinking faith in markets led many to view speculative investments as fundamentally safe. The crisis seemed to have killed off these ideas, but they still live on in the minds of many--members of the public, commentators, politicians, economists, and even those charged with cleaning up the mess. In Zombie Economics, John Quiggin explains how these dead ideas still walk among us--and why we must find a way to kill them once and for all if we are to avoid an even bigger financial crisis in the future. In a new chapter, Quiggin brings the book up to date with a discussion of the re-emergence of pre-Keynesian ideas about austerity and balanced budgets as a response to recession."--Jacket